Understanding Interactions in a Classroom-As-Organization Using Dynamic Network Analysis. (March 2020) - Cocieru, Ovidiu C.; Katz, Matthew; McDonald, Mark A.
Background: The Classroom-as-Organization (CAO) is an experiential learning course in which students create and manage an organization as part of class activities. Student interaction with peers is an important feature of the CAO. Educators suggested that student interactions in CAOs follow certain patterns, but these observations have not been tested in empirical research.Purpose: The research focused on exploring patterns of interaction in a CAO.Methodology/Approach: Network data were collected from students and instructors at four different times during a two-semester CAO course. The authors then used social status theory, friendship formation literature, and Simulation Investigation for Empirical Network Analysis (SIENA) to test hypotheses about interactions in the CAO.Findings/Conclusions: The authors found evidence that (a) localized informal leaders emerge in the class, (b) reciprocation ties between individuals happens within, but not necessarily between departments, and (c) there is a close connection between class-related interactions and social interactions outside of the class, impacting leadership in the CAO.Implications: Instructors need to pay close attention to understanding and managing interdepartmental relationships in CAOs. Furthermore, educators may only have a limited understanding of CAO group dynamics, given that they may not have a high awareness of student social interactions outside of class.